KALAM MODERN: SEBUAH PARADIGMA BARU - Mukhlis, Febri Hijroh (Jurnal Ilmiah Ilmu Ushuluddin, 2018)
This study highlights the tendency of Ê¿Ilm al-KalÄm or sometimes called "Islamic scholastic theology" which is one of the less developed Islamic studies. The author proposes that developing this study requires criticism and a new, more contextual approach. One of the most urgent in Kalams study is to include contemporary contextual themes such as social, humanity, culture and technology. Therefore, the study orientation of Kalam on the issue of divinity (theocentric) must be transformed into the issue of humanity (anthropocentric). For this reason, Kalams study must be interdisciplinary with the social sciences and other modern humanities.